Thunﬁschfang: bei den Eretriern und Naxiern oder auf? (Aelian. De nat. anim. XV, 5) - Jermakova, Lija (Hyperboreus, 2013)
Aelian in the detailed description of ancient tuna ﬁshing (De nat. anim. XV, 5) mentions that Naxians and Eretrians knew about it according to Herodotus and others. Commonly it is understood in literal sense: inhabitants of Naxos and Eretria use this way of ﬁshing, as Aelian alleges. But arguments, on which this interpretation is based, seem unreliable. More plausible is to see in Aelian’s account an obvious hint at Persian tactics of depopulation, that Herodotus describes using the verb σαγηνεύειν.